2022
DOI: 10.1186/s12917-022-03332-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular confirmation of Brucella suis biovar 2 from slaughtered pigs: an unanticipated biovar from domestic pigs in Egypt

Abstract: Background Brucella suis is a zoonotic pathogen with a serious impact on public health and the pig industry worldwide. Information regarding B. suis in pigs in Egypt is scarce. This study aimed to investigate the prevalence of B. suis in slaughtered domestic pigs at El-Basatin abattoir in Cairo, Egypt. A total of 1,116 domestic pigs slaughtered in 2020 were sampled for Brucella isolation and identification. Identified Brucella isolates were molecularly confirmed at species, and biovar levels us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…B. suis bv 2 may be transmitted to domesticated animals. It has been isolated from domestic pigs in Egypt [ 96 ], but it is rarely described as a cause of human brucellosis among hunters [ 97 ]. Nevertheless, the presence of B. suis bv 2 in wild boars and hares is a potential source of spillover and spill-back infection in wildlife and domestic livestock.…”
Section: Discussionmentioning
confidence: 99%
“…B. suis bv 2 may be transmitted to domesticated animals. It has been isolated from domestic pigs in Egypt [ 96 ], but it is rarely described as a cause of human brucellosis among hunters [ 97 ]. Nevertheless, the presence of B. suis bv 2 in wild boars and hares is a potential source of spillover and spill-back infection in wildlife and domestic livestock.…”
Section: Discussionmentioning
confidence: 99%
“…The previous finding was reported almost 15 years ago and, since this time, no further studies were performed to confirm the association between pigs and HEV infection in Egypt. However, the number of pig abattoirs has been increasing in recent years in Egypt and recent studies have reported that pigs could be a source of infections for Trichinella spiralis and Brucella suis in humans [99,100].…”
Section: Pigsmentioning
confidence: 99%
“…The respiratory tract, gastrointestinal tract, conjunctiva, broken skin, and any mucous membrane that comes into contact with contaminated fluids or tissues are further entry routes for Brucella. In Egypt, B. melitensis is the most prevalent Brucella species in ruminants [3] followed by B. abortus and less frequently by B. suis biovar 1 and 2 [4,5]. Recently, B. canis DNA was detected in the blood of stray and owned dogs in Egypt [6].…”
Section: Introductionmentioning
confidence: 99%